Polycrystal positive electrode active material and preparation method and application thereof
By optimizing the particle size, specific surface area and bulk phase porosity of the polycrystalline positive electrode active material, combined with specific chemical composition and preparation methods, the problems of low energy density and degradation of performance of all-solid lithium-ion batteries are solved, and high energy density and excellent rate performance, first-time Coulomb efficiency and cycling performance are achieved.
Patent Information
- Application Number
- CN202411932661.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The energy density of all-solid-state lithium-ion batteries is low and it is difficult to meet the requirements of high energy density. While high-nickel ternary polycrystalline cathode active materials will lead to degradation of rate performance, first-time Coulomb efficiency and cycling performance while increasing the energy density.
A polycrystalline positive electrode active material is provided, with D50 of 2-9 μm, specific surface area BET≤0.35m2/g, bulk phase porosity≤3%, and primary particle length L is 1 μm≤L≤5 μm. The material is optimized by specific chemical composition and preparation methods, including multiple sintering treatments, optimizing particle structure and surface properties.
The battery's rate performance, first-time Coulomb efficiency, cycle performance and energy density are improved, and the process is simple and the cost is low.
Smart Images

Figure CN119725473A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a polycrystalline positive electrode active material and a preparation method and application thereof. Background Art
[0002] Traditional lithium-ion batteries that use organic liquids as electrolytes have safety risks such as flammability, explosion, and solvent leakage. Compared with lithium-ion batteries with traditional liquid electrolytes, all-solid-state lithium batteries have advantages such as high specific energy and high safety, and are a better choice for solving power battery safety issues. Due to the addition of solid electrolytes in the composite positive electrode system of all-solid-state batteries (currently the solid electrolyte accounts for as much as 30-50% by mass), the proportion of positive electrode active materials in the composite positive electrode is maintained at 50-70%, which ultimately leads to the low energy density of all-solid-state batteries, making it difficult to meet the requirements of high energy density. Therefore, the development of positive electrode active materials with high energy density and suitable for all-solid-state batteries is the key to determining the high energy density of all-solid-state batteries.
[0003] At present, high nickel ternary polycrystalline positive electrode active material LiNi x Co y Mn 1-x-y O2 (NCM) has attracted widespread attention due to its high discharge specific capacity of >200 mAh / g, which can improve the energy density of all-solid-state batteries, but will lead to a decrease in the rate performance, first coulombic efficiency and cycle performance of all-solid-state batteries. Summary of the invention
[0004] The main purpose of the present invention is to provide a polycrystalline positive electrode active material, which can be applied to a battery to improve the rate performance, first coulomb efficiency, cycle performance and energy density of the battery.
[0005] The present invention also provides a method for preparing a polycrystalline positive electrode active material. The method can prepare the polycrystalline positive electrode active material and has simple process and low cost.
[0006] The present invention also provides a composite positive electrode active material. Since the composite positive electrode active material includes the above-mentioned polycrystalline positive electrode active material, the composite positive electrode active material is applied to a battery to improve the battery's rate performance, first coulombic efficiency, cycle performance and energy density.
[0007] The present invention also provides a positive electrode sheet. Since the positive electrode sheet includes the above-mentioned polycrystalline positive electrode active material or composite positive electrode active material, the positive electrode sheet is used in a battery to improve the battery's rate performance, first coulomb efficiency, cycle performance and energy density.
[0008] The present invention also provides a battery. Since the battery comprises the positive electrode sheet, the battery has excellent rate performance, first coulomb efficiency, cycle performance and energy density.
[0009] In a first aspect, the present invention provides a polycrystalline positive electrode active material, wherein the D50 of the polycrystalline positive electrode active material is 2-9 μm, and the specific surface area BET is ≤0.35 m 2 / g, bulk porosity ≤3%;
[0010] The primary particle length L of the polycrystalline positive electrode active material is: 1 μm≤L≤5 μm.
[0011] The polycrystalline positive electrode active material as described above has a chemical composition as shown in Formula 1,
[0012] Li a Ni x Co y M z A α D β E γ G δ O2, Formula 1,
[0013] Wherein, M is Mn and / or Al, A includes at least one of Na, K, Cs, Ca, Sr, Ba, La, and Ce, D includes at least one of Al, Zr, Nb, Ta, Ti, and Y, E includes at least one of F, Cl, Br, and I, G includes at least one of B, P, and S, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.20, 0.0005≤α≤0.01, 0.0005≤β≤0.01, 0≤γ≤0.01, 0.0005≤δ≤0.01, x+y<0, and z=1-xy.
[0014] In the polycrystalline positive electrode active material as described above, the primary particles of the polycrystalline positive electrode active material are arranged radially.
[0015] The polycrystalline positive electrode active material as described above has a chemical composition shown in Formula 2,
[0016] Li b Ni o Co p N q H ε J ζ L η O2, Formula 2,
[0017] Wherein, N is Mn and / or Al, H includes at least one of Sr, Y, Al, Zr, Ti, Ce, and La, J includes at least one of Nb, Ta, W, Mo, and Sb, L includes at least one of F, Cl, Br, I, B, P, and S, 0.95≤b≤1.05, 0.80≤o<0.98, 0.02≤p≤0.20, 0.0005≤ε≤0.01, 0.0005≤ζ≤0.01, 0.0005≤η≤0.01, o+p<0, and q=1-op.
[0018] For the polycrystalline positive electrode active material as described above, the angle θ between the longitudinal axis of the primary particle of the polycrystalline positive electrode active material and the diameter line passing through the center of the cross section of the polycrystalline positive electrode active material is ≤20°.
[0019] The polycrystalline positive electrode active material as described above has a primary particle width D of D<1 μm and an aspect ratio L / D of 2≤L / D≤20.
[0020] As described above, the polycrystalline positive electrode active material has a primary particle width D of 1 μm≤D≤3 μm, and an aspect ratio L / D of 0.5≤L / D≤3.
[0021] The polycrystalline positive electrode active material as described above, wherein the SPAN of the polycrystalline positive electrode active material is ≤ 0.7.
[0022] The polycrystalline positive electrode active material as described above has a surface roughness Ra≤1 μm.
[0023] The polycrystalline positive electrode active material as described above, wherein the circularity Re of the polycrystalline positive electrode active material is ≥ 0.90; and / or,
[0024] The particle strength Rσ of the polycrystalline positive electrode active material is 50-500 MPa.
[0025] In a second aspect, the present invention provides a method for preparing the polycrystalline positive electrode active material as described above, characterized in that it comprises the following steps:
[0026] 1) sintering a first system including a polycrystalline positive electrode active material precursor, a first lithium source, an A source or an H source, and a D source or a J source in an oxygen-containing atmosphere for 8-20 hours at 700-900° C. to obtain a first mixture;
[0027] 2) performing secondary sintering on the second system at 600-750° C. for 8-20 hours to obtain a second mixture; wherein the second system includes the first mixture and Co element or the second system includes the first mixture;
[0028] 3) sintering the third system including the second mixture and the G source or the L source three times at 150-350° C. for 8-20 hours to obtain the polycrystalline positive electrode active material.
[0029] In the preparation method as described above, the source of A is an oxide or a halide.
[0030] In a third aspect, the present invention provides a composite positive electrode active material, comprising the polycrystalline positive electrode active material as described above, or the polycrystalline positive electrode active material prepared by the preparation method as described above, and a solid electrolyte.
[0031] The composite positive electrode active material as described above, wherein the ionic conductivity of the composite positive electrode active material is ≥10 -4 S / cm, electronic conductivity ≥10 -4 S / cm.
[0032] In the composite positive electrode active material as described above, the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte is 85-90:10-15.
[0033] In a fourth aspect, the present invention provides a positive electrode sheet, comprising the polycrystalline positive electrode active material as described above, the polycrystalline positive electrode active material prepared by the preparation method as described above, or the composite positive electrode active material as described above.
[0034] In a fifth aspect, the present invention provides a battery comprising the positive electrode sheet as described above.
[0035] The polycrystalline positive electrode active material provided by the present invention limits the D50, specific surface area BET, bulk porosity and primary particle length L of the material, so that it can be applied to a battery, thereby improving the rate performance, first coulomb efficiency, cycle performance and energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 This is a SEM image of the polycrystalline positive electrode active material prepared in Example 1 (magnification is 1K);
[0038] Figure 2 This is a SEM image of the polycrystalline positive electrode active material prepared in Example 1 (magnification is 5K);
[0039] Figure 3This is a SEM image of the polycrystalline positive electrode active material prepared in Example 2 (magnification is 13K);
[0040] Figure 4 This is a SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 1 (magnification is 1K);
[0041] Figure 5 This is a SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 1 (magnification is 5K);
[0042] Figure 6 This is a SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 2 (magnification is 13K);
[0043] Figure 7 Schematic diagram of the angle between the longitudinal axis of a primary particle of a polycrystalline positive electrode active material and a diameter line passing through the center of a cross section of the polycrystalline positive electrode active material. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] In a first aspect, the present invention provides a polycrystalline positive electrode active material, wherein the D50 of the polycrystalline positive electrode active material is 2-9 μm, and the specific surface area BET is ≤0.35 m 2 / g, bulk porosity ≤3%;
[0046] The primary particle length L of the polycrystalline positive electrode active material is: 1 μm≤L≤5 μm.
[0047] The polycrystalline positive electrode active material of the present invention is applied to the battery to improve the rate performance, first coulomb efficiency and cycle performance of the battery. The polycrystalline positive electrode active material is mixed with a solid electrolyte and used in a solid-state battery to significantly improve the energy density of the solid-state battery. It is speculated that this may be due to the D50 of the polycrystalline positive electrode active material being 2-9 μm and the specific surface area BET ≤ 0.35 m 2 / g, bulk porosity ≤3%, primary particle length L: 1μm≤L≤5μm, which can reduce the transmission path of lithium ions and avoid inducing side reactions. It can also make the compaction density of polycrystalline positive electrode active materials higher, reduce the thickness of battery pole pieces, and be beneficial to the rapid transmission of lithium ions and improve the rate performance of the battery. In addition, a smaller BET is beneficial to reduce the interfacial side reactions between polycrystalline positive electrode active materials and electrolyte materials, thereby improving the rate performance, first coulomb efficiency, cycle performance and energy density of the battery.
[0048] The polycrystalline positive electrode active material provided by the present invention limits the D50, specific surface area BET, bulk porosity and primary particle length L of the material, so that it can be applied to a battery, thereby improving the rate performance, first coulomb efficiency, cycle performance and energy density of the battery.
[0049] In some embodiments of the present invention, the polycrystalline positive electrode active material has a chemical composition as shown in Formula 1,
[0050] Li a Ni x Co y M z A α D β E γ G δ O2, Formula 1,
[0051] Wherein, M is Mn and / or Al, A includes at least one of Na, K, Cs, Ca, Sr, Ba, La, and Ce, D includes at least one of Al, Zr, Nb, Ta, Ti, and Y, E includes at least one of F, Cl, Br, and I, G includes at least one of B, P, and S, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.20, 0.0005≤α≤0.01, 0.0005≤β≤0.01, 0≤γ≤0.01, 0.0005≤δ≤0.01, x+y<0, and z=1-xy.
[0052] In the present invention, A includes at least one of Na, K, Cs, Ca, Sr, Ba, La, and Ce, and preferably A includes at least one of Sr, Ba, and Ce; D includes at least one of Al, Zr, Nb, Ta, Ti, and Y, and preferably D includes at least one of Al and Zr; E includes at least one of F, Cl, Br, and I, and preferably E includes at least F; G includes at least one of B, P, and S, and preferably G includes at least two of B, P, and S.
[0053] In the chemical formula of the polycrystalline positive electrode active material of the present invention, the A element acts as a cosolvent to increase the surface energy of primary particles, promote grain growth, and reduce the porosity inside the material; the D element acts as a lattice stabilizer, which is beneficial to the specific capacity of the polycrystalline positive electrode active material, thereby improving the energy density of the battery; the G element is coated on the surface of the polycrystalline positive electrode active material, improves the interface stability between the polycrystalline positive electrode active material and the electrolyte, and improves the cycle performance of the battery.
[0054] In some embodiments of the present invention, the primary particles of the polycrystalline positive electrode active material are arranged radially.
[0055] The primary particles of the polycrystalline positive electrode active material in the present invention are arranged radially, and the stress generated during the charge and discharge process can be released in the radial direction, so that the strain caused by volume expansion is relieved. This radially arranged structure can reduce the strain caused by stress and alleviate the generation of microcracks at the grain boundaries, thereby further improving the cycle performance of the battery. In addition, the radial arrangement can reduce the diffusion distance of ions inside the particles and reduce the transmission barriers of electrons between particles, which helps to improve the ionic conductivity and electronic conductivity of the polycrystalline positive electrode active material, thereby improving the energy density, rate performance and first coulomb efficiency of the battery.
[0056] In some embodiments of the present invention, the polycrystalline positive electrode active material has a chemical composition shown in Formula 2,
[0057] Li b Ni o Co p N q H ε J ζ L η O2, Formula 2,
[0058] Wherein, N is Mn and / or Al, H includes at least one of Sr, Y, Al, Zr, Ti, Ce, and La, J includes at least one of Nb, Ta, W, Mo, and Sb, L includes at least one of F, Cl, Br, I, B, P, and S, 0.95≤b≤1.05, 0.80≤o<0.98, 0.02≤p≤0.20, 0.0005≤ε≤0.01, 0.0005≤ζ≤0.01, 0.0005≤η≤0.01, o+p<0, and q=1-op.
[0059] In the present invention, H includes at least one of Sr, Y, Al, Zr, Ti, Ce, and La, and preferably H includes at least one of Sr, Y, Al, and Zr; J includes at least one of Nb, Ta, W, Mo, and Sb; L includes at least one of F, Cl, Br, I, B, P, and S, and preferably L includes at least two of B, P, and S.
[0060] In the chemical formula of the polycrystalline positive electrode active material of the present invention, the H element acts as a lattice stabilizer, which is beneficial to the specific capacity of the polycrystalline positive electrode active material, thereby improving the energy density of the battery; the J element acts as a grain boundary inhibitor, which can inhibit the coarsening of primary particles of the polycrystalline positive electrode active material, so that it can better maintain a radially arranged structure, alleviate the generation of stress-induced grain boundary microcracks during the charge and discharge process of the battery, and improve the ionic conductivity and electronic conductivity of the polycrystalline positive electrode active material, thereby further improving the rate performance, first coulomb efficiency and cycle performance of the battery.
[0061] In some embodiments of the present invention, an angle θ between a longitudinal axis of a primary particle of the polycrystalline positive electrode active material and a diameter line passing through the center of a cross section of the polycrystalline positive electrode active material is ≤20°.
[0062] like Figure 7 As shown, the angle θ between the longitudinal axis of the primary particle of the polycrystalline positive electrode active material in the present invention and the diameter line passing through the center of the cross section of the polycrystalline positive electrode active material is ≤20°, which is beneficial to maintain the radial arrangement of the polycrystalline positive electrode active material, alleviate the generation of stress-induced grain boundary microcracks during the charge and discharge process of the battery, and improve the ionic conductivity and electronic conductivity of the polycrystalline positive electrode active material, thereby further improving the battery's rate performance, first coulomb efficiency, cycle performance and energy density.
[0063] In some embodiments of the present invention, the primary particle width D of the polycrystalline positive electrode active material is: D<1 μm, and the aspect ratio L / D is: 2≤L / D≤20.
[0064] The width D of the primary particles of the polycrystalline positive electrode active material in the present invention is less than 1 μm, and the aspect ratio L / D is: 2≤L / D≤20, which is further beneficial to maintain the radial arrangement of the polycrystalline positive electrode active material, thereby further improving the rate performance, first coulombic efficiency, cycle performance and energy density of the battery.
[0065] In some embodiments of the present invention, the primary particle width D of the polycrystalline positive electrode active material is: 1 μm≤D≤3 μm, and the aspect ratio L / D is: 0.5≤L / D≤3.
[0066] In the present invention, the primary particle width D of the polycrystalline positive electrode active material is: 1μm≤D≤3μm, and the aspect ratio L / D is: 0.5≤L / D≤3, which is conducive to forming a polycrystalline positive electrode active material with a suitable particle size, can reduce the transmission path of lithium ions, reduce the occurrence of side reactions, and improve the ionic conductivity and electronic conductivity of the polycrystalline positive electrode active material, thereby improving the battery's rate performance, first coulomb efficiency, cycle performance and energy density.
[0067] In some embodiments of the present invention, the SPAN of the polycrystalline positive electrode active material is ≤ 0.7.
[0068] The particle size distribution SPAN of the polycrystalline positive electrode active material of the present invention is small, indicating that the particle size is relatively uniform, the gaps and irregularities between the particles are reduced, the ion transmission path is optimized, the electron transmission resistance is reduced, and it is beneficial to improve the diffusion rate of ions, improve the charge and discharge efficiency, rate performance, first coulomb efficiency and cycle performance of the battery. At the same time, a compact stacking structure can be formed to improve the energy density of the battery.
[0069] The SPAN of the polycrystalline positive electrode active material is calculated according to the formula (D90-D10) / D50. The present invention does not limit the specific values of D90, D50, and D10 of the polycrystalline positive electrode active material, as long as the particle size distribution SPAN of the polycrystalline positive electrode active material is within the above range.
[0070] In some embodiments of the present invention, the surface roughness Ra of the polycrystalline positive electrode active material is ≤1 μm.
[0071] The surface roughness Ra of the polycrystalline positive electrode active material in the present invention is ≤1 μm, which can improve the interface stability between the polycrystalline positive electrode active material and the electrolyte, reduce the interface impedance, and is beneficial to improving the conductivity of ions and electrons, thereby improving the rate performance, first coulomb efficiency, cycle performance and energy density of the battery.
[0072] In some embodiments of the present invention, the circularity Re of the polycrystalline positive electrode active material is ≥ 0.90; and / or,
[0073] The particle strength Rσ of the polycrystalline positive electrode active material is 50-500 MPa.
[0074] The particle strength Rσ of the polycrystalline positive electrode active material in the present invention is within an appropriate range, and can withstand greater mechanical stress during the charge and discharge process, reducing the risk of particle breakage, thereby improving the cycle performance of the battery; in addition, it can also reduce the loss of active materials caused by particle breakage and improve the capacity retention rate of the battery. At the same time, the polycrystalline positive electrode active material with appropriate strength has good processability, reducing the risk of particle breakage during processing.
[0075] The polycrystalline positive electrode active material in the present invention has a high circularity and good contact with the electrolyte, which can optimize the ion transmission path, reduce the electron transmission resistance, and improve the battery's rate performance, first coulomb efficiency, cycle performance and energy density.
[0076] In a second aspect, the present invention provides a method for preparing the polycrystalline positive electrode active material as described above, characterized in that it comprises the following steps:
[0077] 1) sintering a first system including a polycrystalline positive electrode active material precursor, a first lithium source, an A source or an H source, and a D source or a J source in an oxygen-containing atmosphere for 8-20 hours at 700-900° C. to obtain a first mixture;
[0078] 2) performing secondary sintering on the second system at 600-750° C. for 8-20 hours to obtain a second mixture; wherein the second system includes the first mixture and Co element or the second system includes the first mixture;
[0079] 3) sintering the third system including the second mixture and the G source or the L source three times at 150-350° C. for 8-20 hours to obtain the polycrystalline positive electrode active material.
[0080] In the present invention, the polycrystalline positive electrode active material of the first aspect of the present invention can be prepared by subjecting the raw material to three sintering treatments.
[0081] Specifically, in step 1), the first lithium source can be at least one of lithium hydroxide, lithium carbonate, and lithium dihydrogen phosphate. The A source can be a compound containing the A element. As a solubility promoter, it can promote the coarsening of primary particles during the sintering process, reduce the specific surface area of the material, and reduce the porosity inside the material, thereby improving the initial coulombic efficiency and rate performance of the battery; the D source and the H source can be oxides containing the D element or oxides containing the H element. As lattice stabilizers, they are beneficial to stabilize the structural stability of the polycrystalline positive electrode active material and inhibit the release of lattice oxygen, thereby improving the long cycle performance of the battery; the J source can be an oxide containing the J element. As a grain boundary inhibitor, it can inhibit the coarsening of primary particles of the polycrystalline positive electrode active material, so that it can better maintain a radially arranged structure. The present invention does not limit the specific form of the polycrystalline positive electrode active material precursor, as long as it can provide Ni, Co, and M elements. For example, it can be prepared by a coprecipitation method (Ni x Co y M 1-x-y )(OH)2、(Ni x Co y M 1-x-y )CO3、(Ni x Co y M 1-x-y ) x At least one of the precursors.
[0082] In step 2), in one embodiment, the first mixture obtained in step 1) is directly subjected to secondary sintering; in another embodiment, Co element is added to the first mixture to form a second system, and the second system is subjected to secondary sintering to coat or dope the surface of the material with Co element. Both embodiments can improve the surface kinetics of the polycrystalline positive active material or repair the surface oxygen defects, making the material structure more compact and reducing the porosity, thereby improving the rate performance, first coulomb efficiency, cycle performance and energy density of the battery.
[0083] In step 3), the three sinterings can be carried out in oxygen, air or inert atmosphere. The G source or L source is added for the three sinterings, the purpose of which is to coat the G source or L source on the surface of the polycrystalline positive electrode active material, improve the interface stability between the polycrystalline positive electrode active material and the electrolyte, and improve the cycle performance of the battery.
[0084] The preparation method of the present invention can prepare the polycrystalline positive electrode active material of the first aspect mentioned above, and the polycrystalline positive electrode active material is applied to a battery to improve the rate performance, first coulombic efficiency, cycle performance and energy density of the battery.
[0085] In some embodiments of the present invention, the source of A is an oxide or a halide.
[0086] When source A in the present invention is an oxide or a halide, the dissolution effect as a co-solvent is better, which can further reduce the sintering temperature, reduce the lithium-nickel mixing of the polycrystalline positive electrode active material, improve the stability of the battery, improve the ion and electronic conductivity, and further improve the battery's rate performance, first coulomb efficiency, cycle performance and energy density.
[0087] The surface roughness Ra of the polycrystalline positive electrode active material in the present invention is affected by the temperature and time of the primary sintering and the type of the A source.
[0088] The particle strength Rσ, primary particle length L and width D, specific surface area BET, and bulk porosity of polycrystalline positive electrode active materials are affected by the primary sintering temperature and time.
[0089] The radial arrangement of the polycrystalline positive electrode active material is affected by the temperature and time of the primary sintering, and the A source or H source, D source or J source.
[0090] The circularity Re, D50 and SPAN of polycrystalline positive electrode active materials are affected by the precursor of the polycrystalline positive electrode active material.
[0091] In a third aspect, the present invention provides a composite positive electrode active material, comprising the polycrystalline positive electrode active material as described above, or the polycrystalline positive electrode active material prepared by the preparation method as described above, and a solid electrolyte.
[0092] The composite positive electrode active material of the present invention comprises the above-mentioned polycrystalline positive electrode active material and a solid electrolyte. Therefore, the composite positive electrode active material is applied to a battery to improve the rate performance, first coulomb efficiency, cycle performance and energy density of the battery. Among them, the solid electrolyte can be at least one of an oxide solid electrolyte, a halide solid electrolyte and a sulfide solid electrolyte. The oxide solid electrolyte can be at least one of LATP, LLZO and LLTO materials. The halide solid electrolyte can be Li3InCl6, Li2ZrCl6, Li2YZrCl6, LiNbOCl4, LiTaOCl4, Li3ZrCl4O 1.5 At least one of the materials, the sulfide solid electrolyte can be Li2S-P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li 7- x PS 6-x Cl x (0<x<1.7), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 10 GeP2S 12 At least one of the materials.
[0093] The preparation method of the composite positive electrode active material of the present invention may include the following steps: after physically mixing the polycrystalline positive electrode active material and the solid electrolyte in a certain proportion, the solid electrolyte is evenly coated on the surface of the polycrystalline positive electrode active material to obtain a mixed system, and then the mixed system is heat-treated for 1-5 hours at 0-300°C, preferably 50-150°C, under the protection of an inert gas to obtain a composite positive electrode active material. The physical mixing may be ball milling, degassing or banburying, and the mixing time may be 0.5-3 hours.
[0094] In some embodiments of the present invention, the ionic conductivity of the composite positive electrode active material is ≥10 -4 S / cm, electronic conductivity ≥10 -4 S / cm.
[0095] The ionic conductivity of the composite positive electrode active material in the present invention is ≥10 -4 S / cm, electronic conductivity ≥10 -4 S / cm, in a higher range, is beneficial to the improvement of rate performance, first coulombic efficiency, cycle performance and energy density in the battery.
[0096] In some embodiments of the present invention, the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte is 85-90:10-15.
[0097] In the composite positive electrode active material of the present invention, the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte is 85-90:10-15, preferably 85:15. The proportion of the polycrystalline positive electrode active material is relatively high, which is beneficial to the specific capacity. Therefore, the composite positive electrode active material is applied to the battery to improve the rate performance, first coulombic efficiency, cycle performance and energy density of the battery.
[0098] In a fourth aspect, the present invention provides a positive electrode sheet, comprising the polycrystalline positive electrode active material as described above, the polycrystalline positive electrode active material prepared by the preparation method as described above, or the composite positive electrode active material as described above.
[0099] The positive electrode sheet provided by the present invention includes a conductive agent and a binder in addition to a polycrystalline positive electrode active material and a composite positive electrode active material. The present invention does not particularly limit the specific types of the conductive agent and the binder. The conductive agent, the binder and other components can be selected from conventional materials in the art. For example, the conductive agent can be selected from at least one of conductive carbon black, carbon nanotubes, vapor-grown carbon fiber (VGCF), conductive graphite, and graphene, and the binder can be selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylate polymers, polyimide, styrene-butadiene rubber, nitrile rubber, and propylene-butadiene rubber.
[0100] Since the positive electrode sheet provided by the present invention includes the above-mentioned polycrystalline positive electrode active material or composite positive electrode active material, the positive electrode sheet is used in a battery to improve the rate performance, first coulomb efficiency, cycle performance and energy density of the battery.
[0101] In a fifth aspect, the present invention provides a battery comprising the positive electrode sheet as described above.
[0102] The battery in the present invention can be a solid-state battery or a liquid battery. When it is a solid-state battery, in addition to the positive electrode sheet, it also includes a solid electrolyte and a negative electrode sheet. Among them, the solid electrolyte can use conventional electrolytes in the art, for example, at least one of the oxide solid electrolytes LATP, LLZO, and LLTO materials, and the halide solid electrolytes Li3InCl6, Li2ZrCl6, Li2YZrCl6, LiNbOCl4, LiTaOCl4, Li3ZrCl4O 1.5 At least one of the materials, sulfide solid electrolyte Li2S-P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li 7-x PS6-x Cl x (0<x<1.7), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 10 GeP2S 12 At least one of the materials. The negative electrode active material in the negative electrode sheet can be at least one of the currently commonly used negative electrode active materials, such as graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.
[0103] When it is a liquid battery, in addition to the positive electrode sheet, it also includes a separator, a negative electrode sheet and an electrolyte. Among them, the composition of the negative electrode sheet can refer to the conventional negative electrode sheet in the art, and the separator can also be a separator conventionally used in the art, such as PP film, PE film, etc.
[0104] Since the battery provided by the present invention includes the above-mentioned positive electrode sheet, the battery has excellent rate performance, first coulomb efficiency, cycle performance and energy density.
[0105] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0106] Example 1
[0107] The preparation method of the composite positive electrode active material of this embodiment comprises the following steps:
[0108] 1) 1 mol of D50 = 7 μm polycrystalline positive electrode active material precursor (Ni 0.95 Co 0.03 Mn 0.02 )(OH)2, 1.04molLiOH·H2O, 0.005molSrO, and 0.009molZrO2 are mixed to obtain a first system, and the first system is placed in an oxygen atmosphere for a primary sintering at a temperature of 710°C for 12h to obtain a first mixture;
[0109] 2) 1 mol of the first mixture and 0.005 mol of Co(OH)2 were mixed to obtain a second system, and the second system was placed in an oxygen atmosphere for secondary sintering at a temperature of 650°C for 12 hours to obtain a second mixture;
[0110] 3) 1 mol of the second mixture was mixed with 0.005 mol of H3BO3 to obtain a third system, and the third system was placed in an oxygen atmosphere and sintered three times at a temperature of 300°C for 12 hours to obtain a polycrystalline positive electrode active material Li 1.02 Ni0.945 Co 0.035 Mn 0.02 Sr 0.005 Zr 0.009 B 0.005 O2; The primary particles of the polycrystalline positive electrode active material are randomly arranged.
[0111] 4) The polycrystalline positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.
[0112] Example 2
[0113] The preparation method of the composite positive electrode active material of this embodiment comprises the following steps:
[0114] 1) 1 mol D50 = 8 μm polycrystalline positive electrode active material precursor (Ni 0.93 Co 0.06 Mn 0.01 )(OH)2, 1.04molLiOH·H2O, 0.005molZrO2, and 0.005molTa2O5 are mixed to obtain a first system, and the first system is placed in an oxygen atmosphere for a primary sintering at a temperature of 725°C for 12h to obtain a first mixture;
[0115] 2) 1 mol of the first mixture and 0.005 mol of Co(OH)2 were mixed to obtain a second system, and the second system was placed in an oxygen atmosphere for secondary sintering at a temperature of 675°C for 12 hours to obtain a second mixture;
[0116] 3) 1 mol of the second mixture was mixed with 0.005 mol of H3BO3 to obtain a third system, and the third system was placed in an oxygen atmosphere and sintered three times at a temperature of 300°C for 12 hours to obtain a polycrystalline positive electrode active material Li 1.02 Ni 0.925 Co 0.065 Mn 0.01 Ta 0.01 Zr 0.005 B 0.005 O2; The primary particles of the polycrystalline positive electrode active material are arranged radially.
[0117] 4) The polycrystalline positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.
[0118] Example 3
[0119] The preparation method of the composite positive electrode active material in Example 3 is basically the same as that in Example 1, except that 0.002 mol CeF3 and 0.009 mol TiO2 are added in step 1) to obtain a polycrystalline positive electrode active material Li 1.02 Ni 0.945 Co 0.035 Mn 0.02 Ce 0.002 Ti 0.009 B 0.005 F 0.006 O2. The primary particles of the polycrystalline positive electrode active material are randomly arranged.
[0120] Example 4
[0121] The preparation method of the composite positive electrode active material of Example 4 is basically the same as that of Example 2, except that 0.005 mol Al2O3 and 0.005 mol Nb2O5 are added in step 1) to obtain a polycrystalline positive electrode active material Li 1.02 Ni 0.925 Co 0.065 Mn 0.01 Nb 0.01 Al 0.01 B 0.005 O2. The primary particles of the polycrystalline positive electrode active material are arranged radially.
[0122] Example 5
[0123] The preparation method of the composite positive electrode active material of Example 5 is basically the same as that of Example 1, except that the size of the precursor D50 is 9 μm, the primary sintering temperature is changed to 725° C., and the secondary sintering temperature is changed to 675° C.
[0124] Example 6
[0125] The preparation method of the composite positive electrode active material of Example 6 is basically the same as that of Example 1, except that the size of the precursor D50 is 6 μm, the primary sintering temperature is changed to 700° C., and the secondary sintering temperature is changed to 650° C.
[0126] Example 7
[0127] The preparation method of the composite positive electrode active material of Example 7 is basically the same as that of Example 1, except that the precursor size D50 is 3 μm, the primary sintering temperature is changed to 730°C, the secondary sintering temperature is changed to 650°C, and the tertiary sintering temperature is 320°C.
[0128] Example 8
[0129] The preparation method of the composite positive electrode active material in Example 8 is basically the same as that in Example 1, except that the secondary sintering temperature is changed to 600° C. and the tertiary sintering temperature is changed to 300° C.
[0130] Example 9
[0131] The preparation method of the composite positive electrode active material of Example 9 is basically the same as that of Example 1, except that the primary sintering temperature is changed to 710°C, the secondary sintering temperature is changed to 650°C, and the tertiary sintering temperature is changed to 320°C.
[0132] Example 10
[0133] The preparation method of the composite positive electrode active material in Example 10 is basically the same as that in Example 1, except that the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte is changed to 90:10.
[0134] Comparative Example 1
[0135] The preparation method of the composite positive electrode active material of Comparative Example 1 comprises the following steps:
[0136] 1) 1 mol D50 = 7 μm polycrystalline positive electrode active material precursor (Ni 0.95 Co 0.03 Mn 0.02 )(OH)2, 1.04 molLiOH·H2O, and 0.009 mol ZrO2 are mixed to obtain a first system, and the first system is placed in an oxygen atmosphere for a first sintering, the first sintering temperature is 710°C, the time is 12 hours, and a first mixture is obtained;
[0137] 2) 1 mol of the first mixture and 0.005 mol of Co(OH)2 were mixed to obtain a second system, and the second system was placed in an oxygen atmosphere for secondary sintering at a temperature of 650°C for 12 hours to obtain a second mixture;
[0138] 3) 1 mol of the second mixture was mixed with 0.005 mol of H3BO3 to obtain a third system, and the third system was placed in an oxygen atmosphere and sintered three times at a temperature of 300°C for 12 hours to obtain a polycrystalline positive electrode active material Li 1.02 Ni 0.945 Co 0.035 Mn0.02 Zr 0.009 B 0.005 O2; The primary particles of the polycrystalline positive electrode active material are randomly arranged.
[0139] 4) The polycrystalline positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.
[0140] Comparative Example 2
[0141] The preparation method of the composite positive electrode active material of Comparative Example 2 comprises the following steps:
[0142] 1) 1 mol D50 = 5 μm polycrystalline positive electrode active material precursor (Ni 0.93 Co 0.06 Mn 0.01 )(OH)2, 1.04 molLiOH·H2O, and 0.005 mol ZrO2 are mixed to obtain a first system, and the first system is placed in an oxygen atmosphere for a first sintering, the first sintering temperature is 725°C, the time is 12 hours, and a first mixture is obtained;
[0143] 2) 1 mol of the first mixture and 0.005 mol of Co(OH)2 were mixed to obtain a second system, and the second system was placed in an oxygen atmosphere for secondary sintering at a temperature of 675°C for 12 hours to obtain a second mixture;
[0144] 3) 1 mol of the second mixture was mixed with 0.005 mol of H3BO3 to obtain a third system, and the third system was placed in an oxygen atmosphere and sintered three times at a temperature of 300°C for 12 hours to obtain a polycrystalline positive electrode active material Li 1.02 Ni 0.925 Co 0.065 Mn 0.01 Zr 0.005 B 0.005 O2; The primary particles of the polycrystalline positive electrode active material are randomly arranged.
[0145] 4) The polycrystalline positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.
[0146] Comparative Example 3
[0147] The preparation method of the composite positive electrode active material of Comparative Example 3 comprises the following steps:
[0148] 1) 1 mol D50 = 3 μm polycrystalline positive electrode active material precursor (Ni 0.95 Co 0.03 Mn 0.02 )(OH)2, 1.04 molLiOH·H2O, and 0.009 mol ZrO2 are mixed to obtain a first system, and the first system is placed in an oxygen atmosphere for a first sintering, the first sintering temperature is 650°C, the time is 12 hours, and a first mixture is obtained;
[0149] 2) 1 mol of the first mixture and 0.005 mol of Co(OH)2 were mixed to obtain a second system, and the second system was placed in an oxygen atmosphere for secondary sintering at a temperature of 600°C for 12 hours to obtain a second mixture;
[0150] 3) 1 mol of the second mixture was mixed with 0.005 mol of H3BO3 to obtain a third system, and the third system was placed in an oxygen atmosphere and sintered three times at a temperature of 300°C for 12 hours to obtain a polycrystalline positive electrode active material Li 1.02 Ni 0.945 Co 0.035 Mn 0.02 Zr 0.009 B 0.005 O2; The primary particles of the polycrystalline positive electrode active material are randomly arranged.
[0151] 4) The polycrystalline positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.
[0152] Comparative Example 4
[0153] The preparation method of the composite positive electrode active material of this comparative example comprises the following steps:
[0154] 1) Polycrystalline positive electrode active material precursor (Ni 0.83 Co 0.12 Mn 0.05 )(OH)2 and lithium hydroxide and doping raw material tantalum pentoxide are placed in a high-speed mixer in a molar ratio of 0.995:1.05:0.0025 for uniform mixing, and then the uniformly mixed materials are placed in an atmosphere tube furnace, a certain amount of oxygen is introduced, and calcined at 730°C for 10 hours, and air flow crushing treatment is performed at the same time, so as to obtain a layered structure polycrystalline positive electrode active material;
[0155] 2) The layered polycrystalline positive electrode active material prepared above was mixed with 0.5wt% of the coating raw material boron dioxide in a high-speed mixer, and then transferred to an atmosphere tube furnace, a certain amount of oxygen was introduced, and calcined at 450°C for 6h to form an oxide coating layer on the surface of the polycrystalline positive electrode active material to obtain the oxide-coated polycrystalline positive electrode active material Li 1.02 Ni 0.83 Co 0.12 Mn 0.05 O2;
[0156] 3) The polycrystalline positive electrode active material in step 2) is crushed and sieved to obtain a ternary polycrystalline positive electrode active material, wherein the Ta element is uniformly doped in the bulk phase structure of the oxide positive electrode active material, and the B element is uniformly coated in the surface layer of the oxide positive electrode active material.
[0157] 4) The polycrystalline positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.
[0158] Comparative Example 5
[0159] The preparation method of the composite positive electrode active material of this comparative example comprises the following steps:
[0160] 1) The coarse particles of lithium hydroxide are crushed by ball milling. The specific operation is as follows: a certain amount of lithium salt is weighed and put into a ball mill, and a certain number of grinding balls are put in. The grinding balls are divided into three sizes: large, medium and small (with diameters of 12 mm, 10 mm and 5 mm, respectively). The number of grinding balls is 20%, 30% and 50%, and the mass ratio of the total mass of the grinding balls to the mass of the lithium salt is about 5:1. Then, the grinding is carried out at a speed of 300 rpm / for 1 hour to obtain fine powder particles of lithium salt;
[0161] 2) Polycrystalline positive electrode active material precursor (Ni 0.9 Co 0.06 Mn 0.04)(OH)2 and the ground lithium hydroxide powder are mixed in a molar ratio of 1.025 and doped with 0.03wt% Al(OH)3, 0.02wt% ZrO2 and 0.03wt% Sr(OH)2 of the precursor mass. The obtained mixture is heated to 730℃ at a rate of 2℃ / min in an oxygen atmosphere, and then sintered at a constant temperature for 14h. The furnace pressure during this process is 30Pa, and a sintered material is obtained; the sintered material is cooled and crushed, and then sieved with an ultrasonic vibration sifter, wherein the vibration frequency of the ultrasonic vibration sifter is 20KHz, and the D50 of the sifted sintered material is 11.5μm;
[0162] 3) The obtained burnt material is coated, and the specific operation is as follows: weigh 1000 sieved burnt material and put it into the reactor, heat it to 120℃, and rotate at 180rpm. Weigh 6000ppm NH4HSO4 and dissolve it in 70g (7wt%) deionized water, then transfer it to the spray system, and add it dropwise to the reactor at a speed of 1.5mL / min. After the solution is dripped, stir for 4h to obtain the coated material, and then cool and sieve it;
[0163] 4) The screened coated material was transferred to a box furnace with an oxygen atmosphere, heated to 400°C at a rate of 2°C / min, and then sintered at a constant temperature for 8 hours to obtain a polycrystalline positive electrode active material.
[0164] 5) The polycrystalline positive electrode active material and the solid electrolyte LPSC are ball-milled to obtain a mixed system, wherein the mass ratio of the polycrystalline positive electrode active material to the solid electrolyte LPSC is 85:15, and the mixing time is 1 hour; the mixed system is heat-treated at 55° C. for 3 hours in a N2 atmosphere to obtain a composite positive electrode active material.
[0165] Test example:
[0166] 1. D50: The particle size of the polycrystalline positive electrode active material powder sample was tested using a laser particle size analyzer (MasterSizer 2000).
[0167] 2. BET: Weigh the total weight of the empty test tube and the stopper, soak the polycrystalline positive electrode active material powder sample to be tested in anhydrous ethanol for 4 hours, then take out the powder sample and put it in an oven at 105°C for half an hour, then put the powder sample into the sample tube, and weigh the total weight of the powder sample, the test tube and the stopper to calculate the sample mass; turn on the degassing station, put the test tube containing the powder sample into the degassing station at a temperature of 105°C, purge with nitrogen (pure nitrogen) for 30 minutes, cool for 15 minutes, and test at a temperature of 25°C and a humidity of 60%; take P / P0 with points in the range of 0.05~0.25 as the x-axis and P / V(P0-P) as the Y-axis, and make a linear fit based on the BET equation to obtain the slope and intercept of the straight line to calculate the BET specific surface area of the powder sample.
[0168] 3. Bulk porosity: The bulk porosity of the material is tested using the N2 adsorption-desorption curve. The value of the bulk porosity is determined based on the test.
[0169] 4. Primary particle length L and width D: Use Image J software to calculate the primary particle size of the sample, using 1 μm as the scale, then measure the length and width of the primary particles, and calculate their aspect ratio through the software.
[0170] 5. Angle θ between the longitudinal axis of the primary particle and the diameter line passing through the center of the cross section of the polycrystalline positive electrode active material: 1) Use GATAN 697 profiling equipment to perform cross-section processing on the polycrystalline positive electrode active material; 2) Place the sample under a scanning electron microscope, select a sample whose cross-section diameter in the cross-section area is consistent with the D50 of the polycrystalline positive electrode active material, and determine the center of the selected sample cross section; 3) Determine the position of the primary particle, draw the contour curve of the cross section of the primary particle, and select the longest distance between two points of the cross-section contour of the primary particle as the longitudinal axis of the primary particle. The midpoint of the longest distance is the center of gravity of the primary particle; 4) Draw a straight line connecting the center of the circle and the center of gravity, and the angle between the straight line and the longitudinal axis of the primary particle is θ.
[0171] 6. Ra: Place the polycrystalline positive electrode active material on the vacuum adsorption stage of the atomic force microscope. The scanning adopts the tapping measurement mode. The AFM scanning range is 18μm×18μm, the scanning points are 256×256, and the single line measurement time is 1.56s. After the scanning is completed, the positive electrode material is selected and the roughness value Ra is directly read.
[0172] 7. SPAN: Use a laser particle size analyzer to test the particle size of polycrystalline positive electrode active materials, read the D10, D50, and D90 values, SPAN = (D90-D10) / D50.
[0173] 8. Rσ: The particle strength of the polycrystalline positive electrode active material was tested using Shimadzu DUH-211S ultramicrodynamic hardness tester.
[0174] 9. Re: Use Metis software to scan the polycrystalline positive electrode active material particles in SEM to obtain the projected area S and perimeter L. The circularity Re calculation formula is: Re=4πS / L 2 .
[0175] 10. Specific capacity: The above-mentioned polycrystalline positive electrode active materials, sulfide solid electrolyte (Li6PS5Cl), and conductive agent (VGCF) were weighed into a mortar at a mass ratio of 85:15:1 and manually mixed for more than 30 minutes to obtain a mixed material, and then 1% by mass (accounting for 1% of the above-mentioned mixed material) of polytetrafluoroethylene particles (PTFE) was added, and the mixture was heated on a heating table at 150°C for 5 minutes and then manually ground into a film to pre-fiberize the PTFE. The obtained film was then heated and rolled on a calender at a rolling temperature of 100°C. The thickness of the obtained film was adjusted by controlling the gap width between the two hot pressing rollers. The composite positive electrode active material film was repeatedly rolled to obtain a shaped composite positive electrode active material film with a thickness of 40-60µm. The composite positive electrode active material film was calendered to the surface of a 15µm thick Al foil current collector to obtain a positive electrode sheet. The above positive electrode sheet is die-cut into a disc with a diameter of 8mm, and then stacked and cold-pressed with Li6PS5Cl sulfide solid electrolyte membrane and LiIn negative electrode in a glove box filled with Ar atmosphere to obtain an all-solid-state battery. At 25°C, it is charged to 4.5V at a constant current rate of 0.1C / 1C, and then charged at a constant voltage at 4.5V to a current equal to 0.05C. The charging capacity at this time is recorded as the first cycle charging capacity. After standing for 5 minutes, it is discharged at a constant current rate of 0.1C / 1C to a voltage of 2.5V. The discharge capacity this time is recorded as the first cycle discharge capacity of the battery.
[0176] 11. First coulombic efficiency: The all-solid-state battery is charged at 25°C at a constant current of 0.2C to 4.3V, and then charged at a constant voltage of 4.3V to a current equal to 0.05C. The charging capacity at this time is recorded as the first cycle charging capacity. After that, it is left to stand for 5 minutes and then discharged at a constant current of 0.2C to a voltage of 2.0V. The discharge capacity this time is recorded as the first cycle discharge capacity of the battery. The obtained discharge capacity / charge capacity is the first coulombic efficiency.
[0177] 12. Energy density: Use a battery charge and discharge tester to charge the battery to 4.5V at 0.2C constant current at 25℃, then charge it at constant voltage until the current drops to 0.05C. After standing for 5 minutes, discharge the battery to 2.5V at 0.2C constant current, and record the battery's first discharge capacity Q. 放 and the first discharge energy E 放 , weigh the battery mass as W, and calculate the mass energy density ED=E 放 / W.
[0178] 13. Rate performance: At 25°C, the all-solid-state battery is charged at a constant current rate of 0.1C to a voltage of 4.5V, then charged at a constant voltage at a voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.1C to a voltage of 2.5V. The capacity at this time is recorded as the discharge capacity at a rate of 0.1C; after standing for 10 minutes, the battery is charged at a constant current rate of 1C to a voltage of 4.5V, then charged at a constant voltage at a voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current rate of 1C to a voltage of 2.5V. The capacity at this time is recorded as the discharge capacity at a rate of 1C. The ratio of the discharge capacity at a rate of 1C to the discharge capacity at a rate of 0.1C is the 1C rate performance.
[0179] 14. Cycle performance: The all-solid-state battery is charged at a constant current of 0.1C to a voltage of 4.5V at 25°C, then charged at a constant voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current of 0.1C to a voltage of 2.5V. This cycle test is repeated until the capacity decays to 80%, and the number of cycles is recorded.
[0180] Figure 1 This is a SEM image of the polycrystalline positive electrode active material prepared in Example 1 (magnification is 1K).
[0181] from Figure 1 It can be seen that the polycrystalline positive electrode active material prepared in Example 1 is formed by aggregation of primary particles.
[0182] Figure 2 This is a SEM image of the polycrystalline positive electrode active material prepared in Example 1 (magnification is 5K).
[0183] from Figure 2 It can be seen that the primary particles of the polycrystalline positive electrode active material prepared in Example 1 are relatively large.
[0184] Figure 3 This is the SEM image of the polycrystalline positive electrode active material prepared in Example 2.
[0185] from Figure 3 It can be seen that the cross section of the polycrystalline positive electrode active material prepared in Example 2 is arranged radially.
[0186] Figure 4 This is the SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 1 (magnification is 1K).
[0187] from Figure 4 It can be seen that the polycrystalline positive electrode active material prepared in Comparative Example 1 is formed by aggregation of primary particles.
[0188] Figure 5This is the SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 1 (magnification is 5K).
[0189] from Figure 5 It can be seen that the primary particles of the polycrystalline positive electrode active material prepared in Comparative Example 1 are relatively small.
[0190] Figure 6 This is the SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 2.
[0191] from Figure 6 It can be seen that the cross section of the polycrystalline positive electrode active material prepared in Comparative Example 2 is randomly arranged.
[0192] Table 1
[0193]
[0194] Table 2
[0195]
[0196] It can be seen from Table 1-2 that, compared with the comparative example, the polycrystalline positive electrode active material provided by the present invention limits the D50, specific surface area BET, bulk porosity and primary particle length L of the material, so that it can be applied to the battery, which can improve the battery's rate performance, first coulombic efficiency, cycle performance and energy density.
[0197] From the comparison between Examples 1-10 and Comparative Examples 1-5, it can be seen that the polycrystalline positive electrode active material provided by the present invention is applied to a battery, which can improve the rate performance, first coulombic efficiency, cycle performance and energy density of the battery.
[0198] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A polycrystalline positive electrode active material, characterized in that: The D50 of the polycrystalline positive electrode active material is 2-9 μm, and the specific surface area BET is ≤0.35 m 2 / g, bulk porosity ≤3%; The primary particle length L of the polycrystalline positive electrode active material is: 1 μm≤L≤5 μm.
2. The polycrystalline positive electrode active material according to claim 1, characterized in that: The polycrystalline positive electrode active material has a chemical composition shown in Formula 1, Li a Ni x Co y M z A α D β E γ G δ O2, Formula 1 Wherein, M is Mn and / or Al, A includes at least one of Na, K, Cs, Ca, Sr, Ba, La, and Ce, D includes at least one of Al, Zr, Nb, Ta, Ti, and Y, E includes at least one of F, Cl, Br, and I, G includes at least one of B, P, and S, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.20, 0.0005≤α≤0.01, 0.0005≤β≤0.01, 0≤γ≤0.01, 0.0005≤δ≤0.01, x+y<0, and z=1-xy.
3. The polycrystalline positive electrode active material according to claim 1, characterized in that: The primary particles of the polycrystalline positive electrode active material are arranged radially.
4. The polycrystalline positive electrode active material according to claim 3, characterized in that: The polycrystalline positive electrode active material has a chemical composition shown in Formula 2, Li b Ni o Co p N q H ε J ζ L η O2, formula 2, Wherein, N is Mn and / or Al, H includes at least one of Sr, Y, Al, Zr, Ti, Ce, and La, J includes at least one of Nb, Ta, W, Mo, and Sb, L includes at least one of F, Cl, Br, I, B, P, and S, 0.95≤b≤1.05, 0.80≤o<0.98, 0.02≤p≤0.20, 0.0005≤ε≤0.01, 0.0005≤ζ≤0.01, 0.0005≤η≤0.01, o+p<0, and q=1-op.
5. The polycrystalline positive electrode active material according to claim 3 or 4, characterized in that: The angle θ between the longitudinal axis of the primary particle of the polycrystalline positive electrode active material and the diameter line passing through the center of the cross section of the polycrystalline positive electrode active material is ≤20°.
6. The polycrystalline positive electrode active material according to any one of claims 3 to 5, characterized in that: The primary particle width D of the polycrystalline positive electrode active material is: D<1μm, and the aspect ratio L / D is: 2≤L / D≤20.
7. The polycrystalline positive electrode active material according to claim 1 or 2, characterized in that: The primary particle width D of the polycrystalline positive electrode active material is: 1 μm≤D≤3 μm, and the aspect ratio L / D is: 0.5≤L / D≤3.
8. The polycrystalline positive electrode active material according to any one of claims 1 to 7, characterized in that: The SPAN of the polycrystalline positive electrode active material is ≤0.
7.
9. The polycrystalline positive electrode active material according to any one of claims 1 to 8, characterized in that: The surface roughness of the polycrystalline positive electrode active material is Ra≤1 μm.
10. The polycrystalline positive electrode active material according to any one of claims 1 to 9, characterized in that: The circularity Re of the polycrystalline positive electrode active material is ≥ 0.90; and / or, The particle strength Rσ of the polycrystalline positive electrode active material is 50-500 MPa.
11. A method for preparing a polycrystalline positive electrode active material according to any one of claims 1 to 10, characterized in that: The following steps are involved: 1) sintering a first system including a polycrystalline positive electrode active material precursor, a first lithium source, an A source or an H source, and a D source or a J source in an oxygen-containing atmosphere for 8-20 hours at 700-900° C. to obtain a first mixture; 2) performing secondary sintering on the second system at 600-750° C. for 8-20 hours to obtain a second mixture; wherein the second system includes the first mixture and Co element or the second system includes the first mixture; 3) sintering the third system including the second mixture and the G source or the L source three times at 150-350° C. for 8-20 hours to obtain the polycrystalline positive electrode active material.
12. The preparation method according to claim 11, characterized in that: The A source is an oxide or a halide.
13. A composite positive electrode active material, characterized in that: It comprises the polycrystalline positive electrode active material according to any one of claims 1 to 10, or the polycrystalline positive electrode active material prepared by the preparation method according to claim 11 or 12, and a solid electrolyte.
14. The composite positive electrode active material according to claim 13, characterized in that: The ionic conductivity of the composite positive electrode active material is ≥10 -4 S / cm, electronic conductivity ≥10 -4 S / cm.
15. The composite positive electrode active material according to claim 13 or 14, characterized in that: The mass ratio of the polycrystalline positive electrode active material to the solid electrolyte is 85-90:10-15.
16. A positive electrode sheet, characterized in that: It comprises the polycrystalline positive electrode active material according to any one of claims 1 to 10, the polycrystalline positive electrode active material prepared by the preparation method according to claim 11 or 12, and the composite positive electrode active material according to any one of claims 13 to 15.
17. A battery, characterized in that: Including the positive electrode sheet as described in claim 16.
Citation Information
Cited By
Composite polycrystalline positive electrode material, electrode plate and all-solid-state battery
CN120453350A